(untitled) (Geo-Eco-Marina, 2018)
The rivers in India are truly speaking not only life-line of masses but also for wild-life. The rivers play a vital role in the lives of the Indian people. The river systems help us in irrigation, potable water, cheap transportation, electricity as well as a source of livelihood for our ever increasing population. Some of the major cities of India are situated at the banks of holy rivers. Proper management of river water is the need of the hour. Indian agriculture largely depends upon Monsoon which is always uncertain in nature. Hence, there is a severe problem of lack of irrigation in one region and water logging in others. Damage to crops due to drought and pitiable drainage facility could be managed. Depleting and decreasing status of water resources may be one of the most critical resource issues of the 21st century. The core objectives of the paper are to study issues and challenges in interlinking of rivers in India and to study environmental impact of Inter-River Linking Project (IRL). At the backdrop of this, the present paper is an attempt to study issues and challenges in interlinking of rivers in India from the point of view of society at large.